Farm animals - Daynes, Katie; Butler, Nickey; MacKinnon, Catherine-Anne.; Fox, Christyan ([Tulsa, OK] : [EDC Pub.], 2007)
How do pigs keep cool? Why do farmers shear their sheep? Which farm animals live underwater? In this book you'll find the answers and lots more facts about farm animals around the world. Farm animals is part of an exciting new series of books for children who are beginning to read on their own. The easy-to-read text has been specially written with the help of a reading expert.
On the farm -- People and far -- Feeding time -- On a ranch -- Laying eggs -- Milking -- Shearing -- Pigs and piglets -- Lambs and calves -- Ducks and geese -- Underwater farms -- Big birds -- Snow and sand -- Crocodile farms -- Glossary of farm words -- Websites to visit -- Index.
Includes index.
Ages 5-7.
IG 710
Accelerated Reader AR
Keywords: Domestic animals -- Juvenile literature; Animals -- Juvenile literature; Domestic animals; Animals